Contemporary politics, communication, and the impact on democracy - Palau-Sampio, Dolors, 1974-; López García, Guillermo; Iannelli, Laura (Advances in public policy and administration (APPA) book series., 2022)
"The loss of credibility of traditional media and democratic institutions points to the important challenges for the democratic system. Social networks have allowed new political and social actors to disseminate their messages, which has raised diversity. However, it has also lowered the standards for the circulation of messages and has increased disinformation and hate speech. Contemporary Politics, Communication, and the Impact on Democracy addresses communication and politics and the impact on democracy. This book offers a valuable contribution regarding the challenges and threats faced by traditional and stable democracies while disinformation, polarization, and populism have a main role in the present hybrid communicative scenario. Covering topics such as digital authoritarianism, emotional and rational frames, and political conflict on social media, this is an essential resource for political scientists, communication specialists, analysts, policymakers, politicians, critical media scholars, graduate students, professors, researchers, and academicians."--ProQuest website.